(untitled) (Palíndromo, 2021)
The study is a brief intellectual autobiography. It allows its author to understand how a philosophy of art and a philosophy of existence were formed for him on objects as different as art criticism, the music of Monteverdi, the thought of Mallarmé, the theory of the relationship between the arts in the contemporary era or the photography of the mountain landscape and man in high mountains. This philosophy of existence in its artistic, aesthetic and ethical aspects is a philosophy of freedom and perseverance based on the idea of the fragility, vulnerability and precariousness of human life, which is always being tested and constantly reiterated. This philosophy is not fundamentally a disciplinary or academic philosophy. This philosophy cannot be exclusively conceptual since she can be constructed from the images of painting, of photography and literary texts.